Anomalous origin of one pulmonary artery from the ascending aorta (hemitruncus) in a premature infant: A case report and literature review. Issue 6 (31st December 2013) - Bi, Wenjing; Ren, Weidong; Song, Guang; Shang, Cong; Pan, Fuzhi; Xu, Min
ABSTRACT Anomalous origin of one pulmonary artery from the aorta (AOPA) is a rare congenital anomaly. Here, we report the case of a premature infant with a delayed diagnosis of AOPA who died before surgical repair could be attempted, and we review the literature regarding the diagnosis and surgical approaches in premature infants with AOPA. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:367–370, 2014